2008
DOI: 10.2341/07-42
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Enamel Bonding Using Two-step Self-etch Systems on Ground and Unground Enamel

Abstract: The effect of surface preparation was adhesive-dependent. Improvements in resin-enamel bond strength after enamel preparation were observed only for AdheSE and Optibond Solo plus SelfEtch Primer. Among the self-etch systems, mild, self-etch Clearfil SE Bond showed the highest bond strength values. No degradation of resin-enamel bonds was observed after 12 months of water storage, regardless of the adhesive tested. SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 33 publications
(45 reference statements)
0
58
1
3
Order By: Relevance
“…ompared with the stability of resin-enamel bonds (Loguercio et al, 2008), the durability of resin-dentin bonds is relatively poor (see Carrilho et al, 2005, for review). A 30% to 40% decrease in bond strength has often been observed after 3-6 mos of in vitro aging.…”
Section: Introduction Cmentioning
confidence: 99%
“…ompared with the stability of resin-enamel bonds (Loguercio et al, 2008), the durability of resin-dentin bonds is relatively poor (see Carrilho et al, 2005, for review). A 30% to 40% decrease in bond strength has often been observed after 3-6 mos of in vitro aging.…”
Section: Introduction Cmentioning
confidence: 99%
“…Studies revealed that bonding to dentin deteriorates more readily than that to enamel in the long term (De Munck et al, 2003;Loguercio et al, 2008). The hydrolytic and enzymatic breakdown of interfacial collagen is believed to be the leading culprit for such degradation.…”
mentioning
confidence: 99%
“…Clinically, sealants are applied to fissures with intact, aprismatic enamel instead of the ground, prismatic enamel 15 present in the fissure model used in this investigation. However, some authors 16,17 have reported no difference in the adhesion of etch-and-rinse adhesive systems to ground or unground enamel. The use of ground, prismatic tissue in this study most likely did not influence the results since an etch-and-rinse adhesive system was utilized.…”
Section: Discussionmentioning
confidence: 99%